1920
DOI: 10.1017/s0025315400000102
|View full text |Cite
|
Sign up to set email alerts
|

Sea-Temperature, Breeding and Distribution in Marine Animals

Abstract: Breeding in marine animals has long been recognised in a vague way as being in some degree dependent upon sea-temperature. This attitude is well shown in Lo Bianco's last valuable contribution to our knowledge of the breeding periods of practically the whole fauna of the Gulf of Naples. In the Introduction to this work Lo Bianco (1, p. 531) gives tables of temperature observations for a number of years, but does not attempt to correlate them with the breeding periods observed. There are in the literature some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
189
2
7

Year Published

1958
1958
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 432 publications
(214 citation statements)
references
References 3 publications
11
189
2
7
Order By: Relevance
“…Parameters connected with environmental temperature are among the most important physical variables controlling the large-scale distributions and the abundances of marine organisms, though it is often not clear what aspects of temperature are the crucial limiting conditions and what their exact mode of action is (Orton, 1920;Hengeveld, 1990;Bhaud et al, 1995). It is not surprising, thus, that in most scenarios the predicted climate change will have profound implications for ecological conditions (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Parameters connected with environmental temperature are among the most important physical variables controlling the large-scale distributions and the abundances of marine organisms, though it is often not clear what aspects of temperature are the crucial limiting conditions and what their exact mode of action is (Orton, 1920;Hengeveld, 1990;Bhaud et al, 1995). It is not surprising, thus, that in most scenarios the predicted climate change will have profound implications for ecological conditions (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Temperature has been cited as the major environmental factor regulating reproduction in marine bivalves (Sastry, 1979). It has been suggested that the breeding period of a species occurs at characteristic temperatures, which remain a constant throughout the geographical range (Orton, 1920). Gametogenesis is initiated and spawning occurs only within fairly narrow, species-specific temperature ranges.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that gametogenic cycles in marine invertebrates are influenced by exogenous factors (Giese, 1959;Fretter and Graham, 1964;Wilson, 1969;Sastry, 1970Sastry, , 1979Adiyodi and Adiyodi, 1983), of which temperature is believed to be one of the most significant (Orton, 1920;Mann, 1979). Temperature is influential on the onset of both gametogenesis and spawning in many clam species (Calabrese, 1970;Keck et al, 1975;Hesselman et al, 1989;Kanti et al, 1993;Lubet, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The breeding cycles of animals and plants are usually dependent in some way on annual fluctuations in external conditions, particularly temperature and food supply (Orton, 1920;Thorson, 1946;Qasim, 1956;Crisp & Southward, 1958). At Plymouth the same temperature regime is experienced by both A. ecaudata and A. branchialis and the same food supply is available to each.…”
Section: Later Developmentmentioning
confidence: 99%
“…According to Orton (1920), cosmopolitan species should have a wide range of temperature within which breeding can occur; cold-water species near their warmer limits should breed in the colder months of the year; warm-water species near their colder limits should breed in the warmer months of the year. Many organisms have been shown to conform to these conditions, but the two ecaudate species of Arenicola do not.…”
Section: Later Developmentmentioning
confidence: 99%